Rekonstruksi Hak Waris Anak Luar Kawin di Bali menurut Hukum Nasional dan Adat - I Kadek Kharisna Gamentra; I Gede Yusa (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The reconstruction of inheritance rights for out-of-wedlock children in Bali is a significant issue in the dynamic relationship between customary law and national law. In the Balinese customary kinship system, out-of-wedlock children are legally recognized only in relation to their biological mother and have no inheritance rights from their biological father or the father’s relatives. However, following Constitutional Court Decision No. 46/PUU-VIII/2010, there is now an opportunity for out-of-wedlock children to obtain inheritance rights from their biological father if a blood relationship can be scientifically proven. This research applies normative legal methods with statutory and conceptual approaches, examining primary sources from journals and legal research published in the last ten years. The results show that although national law has begun to recognize inheritance rights for out-of-wedlock children, implementation in Balinese customary society still faces challenges, particularly in harmonizing customary values with national legal provisions.